Retroanálise da escolha do tipo da fundação do bloco P da UTFPR Campus Guarapuava - Borges Filho, Alexandre (2019)
The present work consists in comparing different types of foundations, direct and indirect, dimensioned to transmit the loads from the structure to the ground where the P building of the Universidade Tecnológica Federal do Paraná - Guarapuava Campus is located. The foundation system designed for the building consists of the use of continuous propeller piles, which have standardized (constant) lengths for all system units. Therefore, the option adopted in the design of the foundations of the building is evaluated, with the purpose of identifying if this was the best technical and economical solution for the case studied. For the evaluation, both technical aspects, such as execution time, as well as economic aspects were considered, elaboration of budgets using as base the System of Reference Costs of Works (SICRO) and the National System of Costs Research and Indexes of the Construction (SINAPI) and the composition and pricing table for budgets (TCPO). The results show that the solution used was not the best for the relation between loads and soil carrying capacity of the site. Considering the aspects analyzed, it can be concluded that the best choice for this system is based on the use of mechanically dug piles, which can achieve savings of more than 5%. Finally, we discuss the need to change an immediate culture regarding engineering projects, especially with regard to public works.